Gautavik - a trading site in Iceland re-examined (AmS-Skrifter, 2020)
Gautavík is a well-known archaeological site on the east coast of Iceland. It was partially excavated in 1979 and interpreted as a seasonal occupied trading site, abandoned shortly after c. 1500. However, recent archaeological research on the  excavated ceramics, which hitherto had not been studied in detail, raised doubts about the interpretation regarding the dating and function of the site. New research was then initiated that included an investigation of written documents in the archives of Bremen, Hamburg, and Copenhagen, pertaining to the trade with Iceland during the sixteenth century. On the basis of the new results presented here we now interpret Gautavík to have been a trading harbour that also included a farm, at least periodically, occupied from the late twelfth century, at the latest, until shortly before 1600. Gautavík was a place of supra-regional importance, being the main port of entry in Berufjörður during the medieval period. In the sixteenth century, however, Gautavík lost its importance. This was a period of intensive trade of German merchants with Iceland, and after Bremen and Hamburg merchants established Djúpivogur and Fýluvogur at the entrance of the fjord c. 1570, both gradually superseded Gautavík, such that shortly before 1600 trade was no longer conducted there.